2022
DOI: 10.3390/s22020595
|View full text |Cite
|
Sign up to set email alerts
|

Multipurpose Bio-Monitored Integrated Circuit in a Contact Lens Eye-Tracker

Abstract: We present the design, fabrication, and test of a multipurpose integrated circuit (Application Specific Integrated Circuit) in AMS 0.35 µm Complementary Metal Oxide Semiconductor technology. This circuit is embedded in a scleral contact lens, combined with photodiodes enabling the gaze direction detection when illuminated and wirelessly powered by an eyewear. The gaze direction is determined by means of a centroid computation from the measured photocurrents. The ASIC is used simultaneously to detect specific e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
(29 reference statements)
0
3
0
1
Order By: Relevance
“…Another source of improvement consists of using a contact lens eye tracker, as we are developing in parallel [ 20 , 21 ], to simplify gaze detection and improve the headband functionality.…”
Section: Discussionmentioning
confidence: 99%
“…Another source of improvement consists of using a contact lens eye tracker, as we are developing in parallel [ 20 , 21 ], to simplify gaze detection and improve the headband functionality.…”
Section: Discussionmentioning
confidence: 99%
“…IMT Atlantique is one of the pioneers in this emerging field. We have tested the encapsulation of several building bricks (flexible micro-batteries [32], data communication circuits [33] by near field communication (NFC) protocol, ASIC 2 and photodiodes for a centroid calculation [34]) as well as complete functions (double laser pointer [35], eye-tracker, blink detection [36]). We are also one of the few to perform biocompatibility tests (CE marking of our laser pointer).…”
Section: The Visual Hmi Lensmentioning
confidence: 99%
“…IMT Atlantique est un des pionniers dans ce secteur en émergence. Nous avons testé l'encapsulation de plusieurs briques de base (micro-batteries flexibles [32], circuits de communication de données [33] par protocole de communication en champ proche (NFC en anglais), ASIC 2 et photodiodes pour un calcul de barycentre [34]) ainsi que des fonctions complètes (double pointeur laser [35], oculomètre, détection de clignement d'oeil [36]). Nous comptons également parmi les rares à effectuer des tests de biocompatibilité (marquage CE de notre pointeur laser).…”
Section: La Lentille Ihm Visuelunclassified
“…In this paper, we focus on three of them: gaze direction (GD), pupil dilation (PD) and accommodative power (AP). A blinking measurement can also be easily added [2]. Numerous works have shown that these oculometric features provide complementary information about the subject's cognitive load and attention, and yield great benefits when combined.…”
Section: Introductionmentioning
confidence: 99%